ANALISIS PERAN STATUS SOSIAL EKONOMI DALAM MENGAKSES PELAYANAN PUBLIK DI KECAMATAN CIPEUNDEUY - Jenab, Siti; Aryani, Lina; Aditya, Indra (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
In rural areas, accessibility is strongly linked to basic needs, which are indirectly connected to social and economic welfare. A clear disparity exists between urban and rural regions, as well as between the more developed areas of Java and remote regions outside the island. In Cipeundeuy District, with a population of 89,155 and an area of 101.11 km², differences in accessibility are evident, particularly between Cipeundeuy Village, located at the district center, and Margaluyu Village, which is farther away. The geographical distance limits mobility and constrains access to essential public services such as healthcare and education. This study aims to examine the role of socioeconomic status in shaping access to public services at the Cipeundeuy District Office. Employing a qualitative method and the socioeconomic status theory of Horton and Hunt, the research explores how income, occupation, and education influence service accessibility. The findings reveal that higher socioeconomic status does not significantly enhance community access to public services in Cipeundeuy District, highlighting the dominant role of geographical barriers over socioeconomic factors in determining accessibility.